Penggunaan GeoGebra dalam Upaya Peningkatan Minat Siswa SMA dalam Pembelajaran Matematika Materi Program Linear - Fitri Hidayani Sagala, Aisyah; Rahmi Sagala, Maulida (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2023)
Linear program is one of the materials that high school students study. This material is one of the materials that students often find difficult to understand, because basically a linear program is a way to get the best results from a mathematical model consisting of linear relationship. Students often experience problems understanding the steps to find a set of solutions to a linear programming problem. Therefore, as an effort to increase students' interest in linear programming material, this paper discusses the use of GeoGebra as a mathematics learning medium that can be used to help high school students understand linear programming material. This research is a type of quantitative research with quasi-experimental (quasi-experimental), with the population of all classes XI IPA SMA Negeri 11 Medan and the samples of this study were taken as many as two classes from the class XI IPA , which is the class XI IPA 4 as the class of Experiment I and XI IPA 3 as the class of Experiment II. The method of data collection is through a non-test in the form of a questionnaire instrument to determine the student's interest in two classes before and after treatment is given. So that the average N-Gain score was obtained at 0.47 which, if translated into a classification, then the average increase in motivation to learn mathematics among students in this test is in the "moderate" category. With GeoGebra, students can visualize the obtained linear equations and their set of solutions. By looking at the visualization, it is expected that students will be more interested in learning mathematics, especially linear program material